Genghis Khan : creating the Mongol empire - Linde, Barbara M. (World history (Lucent Press), 2018)
Traces the early history and culture of the Mongols, and explores the rise to power of Genghis Khan. Describes Khan's achievements and legacy. Includes a timeline, color illustrations, and further sources.